Parental safety concerns - a barrier to sport and physical activity in children? - Soufiane Boufous; Caroline Finch; Adrian Bauman (Elsevier, 2004)
Abstract Objective: To examine the extent to which parents and carers perceive injury and safety risks as serious enough to prevent or discourage their children, aged 5-12 years, from participating in sports/physical activity and to identify factors that influence these perceptions. Methods: An analysis of the 2001 New South Wales Child Health Survey. Results: More than one‐quarter of parents/carers of active children aged 5-12 years reported discouraging or preventing children from playing a particular sport (34.7% for boys and 16.6% for girls) because of injury and safety concerns. In boys, the most frequently discouraged sport was rugby league (23.2%), followed by rugby union (7.5%) and Australian rules football (2.8%). Among girls, the most frequently discouraged activities were rollerblading (2.7%), rugby league (2.3%) and soccer (2.1%). Multivariate analysis shows that factors independently associated with parents' decision to prevent/discourage their child from engaging in sport/physical activity include their child's age and gender, language spoken at home, presence of disability, and the respondent's relation to the child. Conclusions and implications:Efforts need to be made to modify some sports/ activities, such as football codes, in order to minimise injury and to ensure that children continue enjoying their favourite activity well into adulthood. Guidelines designed to promote physical activity among children and young adolescents need to take into account parental concerns regarding the associated risk of injury.